Energy-Balance-Based Plastic Design and Seismic Fragility Analysis of Steel Plate Shear Wall Coupled with Steel Side Columns - Y. T. Wu; Aozhou Liu; Jiazheng Zhao; Bo Zhang (Advances in Civil Engineering)
The steel plate shear wall (SPSW) coupled with steel side columns (SSCs) through steel coupling beams, or the SPSW–SSC coupled structural system, is a novel lateral force resisting system that introduces coupling mechanism to the isolated SPSW pier. To simplify the complex iteration of the conventional seismic design procedure and obtain the favorable plasticity development and distribution pattern determined by the coupling mechanism, the energy-balance concept and the plastic design method are combined to develop the energy-balance-based plastic design (EBPD) method for the SPSW–SSC coupled system with the consideration of the degradation of hysteretic behavior. Twelve SPSW–SSC coupled system prototype cases with different story numbers and coupling ratios (CRs) were designed and numerically modeled to simulate the main seismic behavior. The pushover analyses and the incremental dynamic analyses were further carried out to examine the lateral load capacity and deformation relationships and the seismic fragility curves with respect to the performance levels quantified by the maximum interstory drift ratios. The analysis results prove that the coupling mechanism can be realized in the SPSW–SSC coupled system with preferred yielding sequence and plasticity distribution mode. The influences of story number and CR on the lateral load capacity curves are revealed. The seismic fragility analysis results indicate the exceeding probability of the limit states corresponding to different performance levels with the consideration of the influences of story number and CR, which further proves the effectiveness of the proposed EBPD methods in terms of the realization of the coupling mechanism and the earthquake collapse safety of the SPSW–SSC coupled structural system.